Efektivitas Penerapan Presensi Fingerprint dan Pengendalian Internal terhadap Disiplin Kerja Pegawai UPTD Puskesmas Kota-1 Kabupaten Mappi, Papua Selatan - Jamlean, Veronica Vensca Inggrid; Andriani, Rian; Rinawati, Rinawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Providing quality public services is a governmental obligation, one of which is by establishing Community Health Centers (UPTD Puskesmas) to deliver healthcare services to all levels of society. Optimal service delivery requires a high level of work discipline; however, there is currently an issue of increasing cases of work discipline violations at UPTD Puskesmas Kota-1. As a consequence, there has been a monthly reduction in BPJS capitation funds received by each staff member. UPTD Puskesmas Kota-1 operates within a specific context that differs from other institutions regarding the measurement of employee work discipline. For example, field assignments often render fingerprint attendance less applicable; therefore, the health center continues to employ a manual system as a complementary method. This study aims to examine the effect of fingerprint attendance systems and internal control on work discipline. Data was collected through questionnaires distributed to 40 employees at UPTD Puskesmas Kota-1. The analytical method used was multiple linear regression. The results show that both fingerprint attendance and internal control have a significant partial effect on work discipline. Simultaneously, the implementation of fingerprint attendance and internal control also significantly influences work discipline, with a coefficient of determination of 46%, while the remaining 54% is influenced by other variables not included in this study.